2020
DOI: 10.3803/enm.2020.35.2.206
|View full text |Cite
|
Sign up to set email alerts
|

Precision Therapy in Acromegaly Caused by Pituitary Tumors: How Close Is It to Reality?

Abstract: Acromegaly presents with an enigmatic range of symptoms and comorbidities caused by chronic and progressive growth hormone elevations, commonly due to endocrinologic hypersecretion from a pituitary gland tumor. Comprehensive national acromegaly databases have been appearing over the years, allowing for international comparisons of data, although still presenting varying prevalence and incidence rates. Lack of large-scale analysis in geographical and ethnic differences in clinical presentation and management re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 76 publications
0
4
0
1
Order By: Relevance
“…Acromegaly is a rare disease characterized by excess growth hormone (GH) and insulin-like growth factor-1 (IGF-1), as well as enlarged bone, soft tissues, and organs. 1 Acromegaly progresses insidiously and slowly; therefore, the average interval from onset of symptoms to diagnosis ranges from 5 to 10 or more years. 2 Long-term exposure to excess GH and IGF-1 can cause multiple systemic complications and increased mortality in patients with acromegaly.…”
Section: Discussionmentioning
confidence: 99%
“…Acromegaly is a rare disease characterized by excess growth hormone (GH) and insulin-like growth factor-1 (IGF-1), as well as enlarged bone, soft tissues, and organs. 1 Acromegaly progresses insidiously and slowly; therefore, the average interval from onset of symptoms to diagnosis ranges from 5 to 10 or more years. 2 Long-term exposure to excess GH and IGF-1 can cause multiple systemic complications and increased mortality in patients with acromegaly.…”
Section: Discussionmentioning
confidence: 99%
“…Нейроэндокринные PIT1-позитивные ГР-продуцирующие опухоли гипофиза Other problems of endocrinology фенотипу. В связи с малой распространенностью биомаркеров, которые могли бы предсказать биологическое поведение опухоли и реакцию на лечение, практикуемая традиционная МТ вынуждена использовать метод проб и ошибок, который не отвечает современным принципам прецизионной и персонализированной терапии [13,14]. К сожалению, независимо от особенностей рецепторного фенотипа СО, всем нуждаю щимся в лечении пациентам в качестве препарата 1-й линии назначаются пролонгированные препараты АС1, эффективность которых в неселективной группе составляет около 40-50% [15].…”
Section: Predictors Of Morphofunctional Features Of Somatotrophic Tum...unclassified
“…The Pituitary Gland -An Overview of Pathophysiology and Current Management Techniques humoral, imaging and pathomorphological predictors for preliminary stratification of clinically homogeneous patients with a clear clinical prognosis and response to treatment [16,17].…”
Section: Tumor-oriented Diagnosis and Treatmentmentioning
confidence: 99%
“…In a prospective study evaluating the effectiveness of lanreotide (120 mg every 28 days) as a first-line therapy, it was shown that the normalization of GH levels and IGF-I after 24 and 48 weeks of treatment were observed in 23.4 and 30.6% of patients. Thus, a significant part of patients receiving fg-SRLs has partial or complete resistance, which is a consequence of the internal heterogeneity of somatotropin in relation to the receptor expression of SSTs and other target molecules affecting the therapeutic response [16][17][18].…”
Section: The Phenomenon Of Resistance To Fg-srlsmentioning
confidence: 99%